PEMANFAATAN KONSEP “MUKA” (FACE) DALAM WACANA WAYANG GOLEK: ANALISIS PRAGMATIK - Dadang Suganda (Humaniora, 2007)
This paper attempts to describe the concept of face found in wayang golek discourse. This descriptive and qualitative study is done under the scope of pragmatics. The concept of face to a certain extent determines how a conversation can be conducted efficiently, effectively, and politely. The concept of face in wayang golek discourse yields two concepts namely positive and negative face concepts.